2021
DOI: 10.3390/toxins13110749
|View full text |Cite
|
Sign up to set email alerts
|

DT389-YP7, a Recombinant Immunotoxin against Glypican-3 That Inhibits Hepatocellular Cancer Cells: An In Vitro Study

Abstract: Hepatocellular carcinoma (HCC) is one of the high-metastatic types of cancer, and metastasis occurs in one-third of patients with HCC. To maintain the effectiveness of drug compounds on cancer cells and minimize their side effects on normal cells, it is important to use new approaches for overcoming malignancies. Immunotoxins (ITs), an example of such a new approach, are protein-structured compounds consisting of toxic and binding moieties which can specifically bind to cancer cells and efficiently induce cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Despite the latest technological advances in conventional therapies, such as chemotherapy and radiotherapy, these techniques still have certain limitations due to the severe side-effects on normal tissue [4]. On the other hand, it has recently been shown that some bacterial toxins have the ability to kill cancer cells or reduce the cellular processes that control proliferation, apoptosis, and differentiation [5][6][7][8][9][10]. For example, the Cytolethal distending toxin (CDT) can induce apoptosis in the majority of human leukemic T cells (MOLT-4) through the caspase-dependent classical pathway [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the latest technological advances in conventional therapies, such as chemotherapy and radiotherapy, these techniques still have certain limitations due to the severe side-effects on normal tissue [4]. On the other hand, it has recently been shown that some bacterial toxins have the ability to kill cancer cells or reduce the cellular processes that control proliferation, apoptosis, and differentiation [5][6][7][8][9][10]. For example, the Cytolethal distending toxin (CDT) can induce apoptosis in the majority of human leukemic T cells (MOLT-4) through the caspase-dependent classical pathway [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The immunotoxin DT389-YP7 was obtained by fusing a truncated diphtheria toxin without a binding domain with a humanized YP7 scFv specific for a highly expressed Glypican-3 antigen on the surface of hepatocarcinoma cells, resulting specifically cytotoxic on the target HepG2 cell line. Cellular morphological changes, cell cycle arrest at the G2 phase, augment in radical oxygen species production, induction of apoptosis, and inhibition of cell movement were observed after the immunotoxin treatment [12]. The two recombinant anti epidermal growth factor receptor (EGFR) conjugates, EGF-PE40 and EGF-PE24mut, were constructed by fusing the epidermal growth factor (EGF) to PE40, which is the natural toxin domain of pseudomonas exotoxin A, or to PE24mut, its de-immunized variant.…”
mentioning
confidence: 99%